2021
DOI: 10.3390/molecules26123577
|View full text |Cite
|
Sign up to set email alerts
|

The Microglial Activation Inhibitor Minocycline, Used Alone and in Combination with Duloxetine, Attenuates Pain Caused by Oxaliplatin in Mice

Abstract: The antitumor drug, oxaliplatin, induces neuropathic pain, which is resistant to available analgesics, and novel mechanism-based therapies are being evaluated for this debilitating condition. Since activated microglia, impaired serotonergic and noradrenergic neurotransmission and overexpressed sodium channels are implicated in oxaliplatin-induced pain, this in vivo study assessed the effect of minocycline, a microglial activation inhibitor used alone or in combination with ambroxol, a sodium channel blocker, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 87 publications
(126 reference statements)
2
8
0
Order By: Relevance
“…Another drug with prominent neuroprotective properties is minocycline. Minocycline is a second-generation semisynthetic tetracycline antibiotic with a good BBB penetration [ 101 ]. Its neuroprotective activity has been shown in various animal models of neuroinflammation including LPS model [ 8 , 102 ].…”
Section: Therapeutic Strategies Targeting Neuroinflammation and Cogni...mentioning
confidence: 99%
“…Another drug with prominent neuroprotective properties is minocycline. Minocycline is a second-generation semisynthetic tetracycline antibiotic with a good BBB penetration [ 101 ]. Its neuroprotective activity has been shown in various animal models of neuroinflammation including LPS model [ 8 , 102 ].…”
Section: Therapeutic Strategies Targeting Neuroinflammation and Cogni...mentioning
confidence: 99%
“…Of note, based on these data and the fact that 35 µM of duloxetine has the capacity to exert significant inhibitory effects on platelet function regardless of the platelet function assay and/or agonist used, this dose was selected for further in vitro experimentation. Following this, we examined its ex vivo effects by injecting mice with 20 mg/kg of duloxetine, which was selected based on a literature review [ 16 , 17 , 18 , 19 , 20 , 21 ], before platelets were collected and their aggregation response examined. Indeed, duloxetine significantly reduced ADP- (58% ± 13), and U46619 (43% ± 11)-induced platelet aggregation ( Figure 1 C,D, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Likely off-target due to high dose [ 31 ] Oxaliplatin-induced neuropathic pain 50–100 mg/kg IP single or repeated dose (for 7 consecutive days starting with oxaliplatin treatment) Reduces tactile allodynia and cold hyperalgesia 1 h and 6 h after administration. Likely off-target due to high doses [ 32 ] Spinal cord injury pain in rats 25 mg/kg IP post-injury for 7, 12, or 16 days Minocycline alone and in combination with botulinum toxin reduces the inflammatory response and oxidative stress of glial cells, activates SIRT1 and restrains pAKT, P53, and pNF-KB. Likely off-target due to high dose [ 33 ] Systemic lipopolysaccharide (LPS)-induced spinal cord inflammation in neonatal rats Single injection 45 mg/kg IP 5 min after LPS injection Reduces LPS-induced allodynia and hyperalgesia.…”
Section: Targeting Neuroinflammation With Approved Drugsmentioning
confidence: 99%
“…It was shown that intrathecal injection reduced mechanical allodynia in vivo and reduced the A1/A2 ratio of spinal astrocytes in a rat model of skin/muscle incision and retraction (SMIR) by downregulating CXCR7 and the PI3K/Akt system [ 30 ]. In the context of chemotherapy-induced neuropathic pain, minocycline treatment reduced vincristine-induced mechanical hypersensitivity in mice, as well as tactile allodynia and cold hyperalgesia caused by oxaliplatin when administered alone or in combination with duloxetine [ 31 , 32 ]. Likewise, minocycline alone and in combination with botulinum toxin decreased the inflammatory response and oxidative stress of glial cells after spinal cord injury pain in rats by activating SIRT1 and restraining pAKT, P53, and p-NF-kB [ 33 ].…”
Section: Targeting Neuroinflammation With Approved Drugsmentioning
confidence: 99%